Heterophase fcc-2H-fcc gold nanorods - Zhanxi Fan (Nature Portfolio, 2020)
The crystal phase-based heterostructures of noble metal nanomaterials are of interest for various applications. Here, the authors report the wet-chemical synthesis of gold nanorods with a well-defined fcc-2H-fcc heterophase, which possess unique optical and catalytic properties.